(untitled) (Global Journal of Human-Social Science, 2020)
Despite having substantial strategy and policy on human resource development, Bangladeshi (BD) workers in Malaysia mostly migrate in the unskilled category. Their capability development training in Malaysia takes place in an informal and unorthodox way through Community of Practice (CoP). This research attempts to investigate the effect of migration management and the workers training and community activities of Terengganu, the east coast of Malaysia, on the QoL of BD migrant workers. Thematic analysis is used in this qualitative research, with the help of atlas ti version seven for data analysis. The research could hardly reveal any existence of community resilience, though hundreds of them are staying together in many construction sites. Meaning, they are staying together but forming a ’Solitary Community’ and leading a lower QoL. The outcome of this research will be useful for experts to further enhance migration, capability expansion, and community development philosophy to improve the migrant workers QoL.